(untitled) (Global Journal of Management and Business Research, 2012)
A conflict in scientific entrepreneurship has arisen over the propriety of scientific advancements, business governance, and the resulting commercializationof scientificinnovations. Some research indicates that the commercialization activities display asymmetric convergence because industry appears to have a more influential role in the exploitation of these innovations. Yet, the research does not differentiate the types of commercialization activities and assumes that all forays into scientific entrepreneurship are comparable. This research aims to explore these contentions and differentiate two groups of scientific entrepreneurs based on their lived experience. This research indicates that, while the essence of the experience is the same, these groups of scientific entrepreneurs have different experiences based on their roles and the conflicts related thereto, witness varying control issues over the fate and delivery of their innovation due to the influences of investor relations, and exhibit differing visions for the future based on their experience. This research provides evidence and advances the theory that scientific entrepreneurs need to be segregated by the influence of their investor relationships because of the differences these relationships impose on their lived experience.